Fundamentals of strategic management - Parthasarthy, Raghavan (Houghton Mifflin Company, 2007)
Fundamentals of Strategic Management emphasizes strategy in action, exposing students to real-world examples, practical applications, and strategic theory. Designed specifically for business majors enrolled in the undergraduate capstone course, this brief text takes a clear, concise approach to strategic management and incorporates material from practitioner sources such as Harvard Business Review and Business Week. The author poses a central question--"What makes a business successful?"--to form the basis of discussion for each chapter. One chapter is devoted entirely to corporate governance and social responsibility; coverage of these timely issues is also integrated throughout the program. Boxed examples, end-of-chapter continuing cases, and diagrams and models enhance students' understanding of management concepts.